A prospective observation on nutrition support in adult patients with severe burns. Issue 9 (4th February 2019) - Guo, Fengmei; Zhou, Hua; Wu, Jian; Huang, Yingzi; Lv, Guozhong; Wu, Yunfu; Zhao, Hongsheng; Jin, Jun; Zhao, Fuli; Liu, Lijun; Liu, Wenming; Yang, Yi; et al.
Abstract: Nutrition therapy is considered an important treatment of burn patients. The aim of the study was to delineate the nutritional support in severe burn patients and to investigate association between nutritional practice and clinical outcomes. Severe burn patients were enrolled ( n 100). In 90 % of the cases, the burn injury covered above 70 % of the total body surface area. Mean interval from injury to nutrition start was 2·4 (sd 1·1) d. Sixty-seven patients were initiated with enteral nutrition (EN) with a median time of 1 d from injury to first feed. Twenty-two patients began with parenteral nutrition (PN). During the study, thirty-two patients developed EN intolerance. Patients received an average of about 70 % of prescribed energy and protein. Patients with EN providing <30 % energy had significantly higher 28- d and in-hospital mortality than patients with EN providing more than 30 % of energy. Mortality at 28 d was 11 % and in-hospital mortality was 45 %. Multiple regression analysis demonstrated that EN providing <30 % energy and septic shock were independent risk factors for 28- d prognosis. EN could be initiated early in severe burn patients. Majority patients needed PN supplementation for energy requirement and EN feeding intolerance. Post-pyloric feeding is more efficient than gastric feeding in EN tolerance and energy supplement. It is difficult for severe burn patients to obtain enough feeding, especially in the early stage of the disease. More than 2 weeks of underfeeding is harmful to recovery.